Can low-wage workers find better jobs? - Todd M. Gabe; Jaison R. Abel; Richard L. Florida (Federal Reserve Bank of New York, 2018)
There is growing concern over rising economic inequality, the decline of the middle class, and a polarization of the U.S. workforce. This study examines the extent to which low-wage workers in the United States transition to better jobs, and explores the factors associated with such a move up the job ladder. Using data covering the expansion following the Great Recession (2011-17) and focusing on short-term labor market transitions, we find that around 70 percent of low-wage workers stayed in the same job, 11 percent exited the labor force, 7 percent became unemployed, and 6 percent switched to a different low-wage job. Troublingly, just slightly more than 5 percent of low-wage workers found a better job within a 12-month period. Study results point to the importance of educational attainment in helping low-wage workers move up the job ladder.
Keywords: J01; J24; J61; J62; 330; low-wage jobs; career ladder; labor market dynamics